Prevalence of needle stick injury among post-graduate residents of medical college in North India: a cross-sectional study - Kaur, Navpreet; Singh, Jasmeet; Mahajan, Sanjeev (International Journal Of Community Medicine And Public Health, 2025)
Background: Needle stick injury (NSI) is a major concern among healthcare professionals especially young resident doctors. As they navigate through their professional journey, these early-career healthcare workers (HCWs) may face heightened exposure to the risk of occupational injuries, including NSIs. Recognizing the importance of addressing this issue, this cross-sectional study was conducted with the objective of determining the prevalence of needle stick injuries among postgraduate students at a medical college in northern India. Methods: A cross-sectional study was conducted among residents of medical college in North India. Data was collected for period of one month. A validated, pre-structured questionnaire was used. Data was compiled using Microsoft Excel and analyzed using Epi-info 7 (CDC USA) freely available online. Results: The prevalence of NSI among post-graduate students was found out to be 55.2%. Half (50%) of these NSI were found out to be un-reported. More than half (58.62%) of study participants didn’t get themselves tested for HBV/HCV/HIV after NSI. Conclusions: High prevalence of NSI was found among post-graduate residents. The knowledge about intricacies of post-exposure prophylaxis (PEP) was found to be lacking. There is need to enhance educational efforts and have strict protocols in place amongst health-care professionals regarding NSI.